2021
DOI: 10.1371/journal.pgph.0000014
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum parasite prevalence in East Africa: Updating data for malaria stratification

Abstract: The High Burden High Impact (HBHI) strategy for malaria encourages countries to use multiple sources of available data to define the sub-national vulnerabilities to malaria risk, including parasite prevalence. Here, a modelled estimate of Plasmodium falciparum from an updated assembly of community parasite survey data in Kenya, mainland Tanzania, and Uganda is presented and used to provide a more contemporary understanding of the sub-national malaria prevalence stratification across the sub-region for 2019. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 90 publications
1
33
0
Order By: Relevance
“…In addition, it was evident that age of the participants, sex, marital status, family size, utilization of LLINs and IRS, proximity to mosquito breeding site, and presence of holes on the wall were determinants of malaria transmission. In the current study, the overall percentage of malaria cases detected was 81 (19%) ( n = 422), with P. vivax being the most prevalent species, is lower than the previous findings from Wolaita Zone (33.27%) [ 21 ], and Hallaba (82.84%) [ 22 ], However, is higher than that reported Sudan (9.1%) [ 23 ] Kenya (18.0%) [ 24 ], Kenya (6.4%), Tanzania (12.1%), and Uganda (6.3%) [ 25 ]. Interestingly, some earlier studies conducted in Ethiopia showed much lower prevalence.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, it was evident that age of the participants, sex, marital status, family size, utilization of LLINs and IRS, proximity to mosquito breeding site, and presence of holes on the wall were determinants of malaria transmission. In the current study, the overall percentage of malaria cases detected was 81 (19%) ( n = 422), with P. vivax being the most prevalent species, is lower than the previous findings from Wolaita Zone (33.27%) [ 21 ], and Hallaba (82.84%) [ 22 ], However, is higher than that reported Sudan (9.1%) [ 23 ] Kenya (18.0%) [ 24 ], Kenya (6.4%), Tanzania (12.1%), and Uganda (6.3%) [ 25 ]. Interestingly, some earlier studies conducted in Ethiopia showed much lower prevalence.…”
Section: Discussionmentioning
confidence: 62%
“…There is also evidence of persistence of proteins that encode for apoptosis after placental malaria has been cleared by pharmaceutical agents [ 22 ]. This study also considered vivax malaria, which is not common in our setting in Uganda, and is less virulent compared to Plasmodium falciparum, that has been found to be more common in our setting [ 23 ] . Another study in Malawi reported adverse birth outcomes due to sequestration of Plasmodium falciparum parasites in the placenta [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sub-Saharan Africa harbors 95% of the global malaria burden 1 . While national surveys conducted by ministries of health throughout Africa regularly assess Plasmodium falciparum burden 2 , little is known about the prevalence and geographic distribution of non-falciparum malaria species, including Plasmodium malariae, Plasmodium vivax, and Plasmodium ovale spp. [3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%